Proyek Berdiferensiasi STEAM dalam Menumbuhkan Jiwa Kepemimpinan dan Sikap Peduli Lingkungan Siswa Sekolah Dasar - Maria Magdalena Sri Wahyuni; Ana Fitrotun Nisa; Heri Maria Zulfiati (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This research aims to describe the development of student leadership and environmental awareness through the implementation of STEAM (Science, Technology, Engineering, Art, and Mathematics)-based differentiated projects. The STEAM approach seeks to cultivate students' leadership qualities and environmental responsibility, both individually and collaboratively, by utilizing real-world challenges as a learning medium. An inclusive learning environment fosters students' ability to manage conflicts, solve problems, communicate effectively, and make responsible decisions. STEAM-based differentiated projects not only strengthen students' skills but also instill important character values, such as empathy, cooperation, and integrity. This research aims to outline the steps involved in implementing STEAM projects and highlight their benefits in both academic achievement and character development. This study employs a qualitative descriptive method. The participants consist of 14 fifth-grade students. Data were collected through observation, interviews, and documentation techniques. The data analysis process involved three stages: data selection, data presentation, and verification or conclusion. The findings from the STEAM-based differentiated project reveal that learning activities resulted in diverse student-created products, demonstrating leadership qualities and environmental care. These products include items made from repurposed materials, posters, and prototypes. This project-based learning approach encourages students to take initiative, express their ideas, and propose solutions to observed environmental issues, thereby fostering positive character traits essential for their future.